Relational Continuity from the Patient Perspective: Comparison of Primary Healthcare Evaluation Instruments - Burge, Frederick (Longwoods Publishing, 2011)
The operational definition of relational continuity is “a therapeutic relationship between a patient and one or more providers that spans various healthcare events and results in accumulated knowledge of the patient and care consistent with the patient's needs.” OBJECTIVE: To examine how well relational continuity is measured in validated instruments that evaluate primary healthcare from the patient's perspective. METHOD: 645 adults with at least one healthcare contact in the previous 12 months responded to six instruments that evaluate primary healthcare. Five subscales map to relational continuity: the Primary Care Assessment Survey (PCAS, two subscales), the Primary Care Assessment Tool – Short Form (PCAT-S) and the Components of Primary Care Index (CPCI, two subscales). Scores were normalized for descriptive comparison. Exploratory and confirmatory (structural equation modelling) factor analysis examined fit to operational definition, and item response theory analysis examined item performance on common constructs. RESULTS: All subscales load reasonably well on a single factor, presumed to be relational continuity, but the best model has two underlying factors corresponding to (1) accumulated knowledge of the patient and (2) relationship that spans healthcare events. Some items were problematic even in the best model. The PCAS Contextual Knowledge subscale discriminates best between different levels of accumulated knowledge, but this dimension is also captured well by the CPCI Accumulated Knowledge subscale and most items in the PCAT-S Ongoing Care subscale. For relationship-spanning events, the items' content captures concentration of care in one doctor; this is captured best by the CPCI Preference for Regular Provider subscale and, to a lesser extent, by the PCAS Visit-Based Continuity subscale and one relevant item in the PCAT-S Ongoing Care subscale. But this dimension correlates only modestly with percentage of reported visits to the personal doctor. The items function as yes/no rather than ordinal options, and are especially informative for poor concentration of care. CONCLUSION: These subscales perform well for key elements of relational continuity, but do not capture consistency of care. They are more informative for poor relational continuity.